Prevalence of Sickle cell disease, Sickle cell trait and HBS-beta-thalassemia in India: A systematic review and Meta-analysis - Priyanka Rao; Elstin Anbu Raj; Senthilkumar Natesan; Nachiket Gudi (Elsevier, 2024)
Background: Sickle Cell Disease (SCD) is a common inherited disease in India. However, more aggregate data regarding the burden and distribution of SCD in India is required. Methods: A search was conducted in five electronic databases between 2000 and 2023. The quality appraisal was performed using the JBI Critical Appraisal Tool for prevalence studies. The review is reported according to the PRISMA guidelines. Results: 87 studies were included in this systematic review. The prevalence of SCD, Sickle cell trait (SCT), and HBS-beta-thalassemia was estimated to be 1.17% (95% CI:0.79%-1.75%), 5.9% (95% CI:3.8%-8.88%) and 0.37% (95% CI:0.17%-0.83%) respectively. Madhya Pradesh, Chhattisgarh, and Maharashtra have a high prevalence of SCD and SCT. The burden is higher among the tribal communities of India. Conclusion: Prioritizing the management of SCD in India through targeted screening among communities of at-risk couples and newborns, and pre-marital counseling and raising awareness can assist in reducing the disease burden.